TEST-RETEST RELIABILITY OF HAND GRIP STRENGTH MEASUREMENT USING A JAMAR HAND DYNAMOMETER IN PATIENTS WITH ACUTE AND CHRONIC CERVICAL RADICULOPATHY (International Journal of Physiotherapy, 2017)
Background: To evaluate the test-retest reliability of Jamar hand held dynamometer for measuring handgrip strength (HGS) in patients with acute and chronic cervical radiculopathy and to find out the difference in measurement of the handgrip strength between acute and chronic cervical radiculopathy.Methods: A prospective, observational and non-experimental, the comparative study design was used. A sample of 72 subjects (37 women and 35 men) suffering from cervical radiculopathy were divided into two groups i.e., Group A(acute) and Group B(chronic), handgrip strength was measured using Jamar hand held dynamometer on two occasions by the same rater with an interval of 7-days. Data collection was based on standard guidelines of American Society of Hand Therapists. Three gripping trials (measured in Kg) with patient’s arm in standardized arm position were recorded. The data was analyzed from the mean score obtained from the sample.Result: One-way Analysis of Variance(ANOVA) was used to evaluate test-retest reliability and Tukey-Kramer Multiple Comparison Test used to find the difference between handgrip strength among acute and chronic Cervical radiculopathy cases. Greater P-value (>0.05) in both testing session, as well as 95% of the confidence interval, shows the reliability of the instrument and lesser p-value (0.05) in female subjects shows no significant difference in handgrip strength between the two groups.Conclusion: Excellent test-retest reliability for hand grip strength measurement was measured in patients with acute and chronic cervical radiculopathy shows that the equipment could be used as an assessment tool for this patient and significant difference exists among male handgrip strength between acute and chronic cervical radiculopathy cases whereas no difference exists among female handgrip strength between acute and chronic cervical radiculopathy cases.